PENGGUNAAN MEDIA KOTAK DAN KARTU MISTERIUS TERHADAP HASIL BELAJAR FISIKA - Silvia, Nike; Jarnawi, Muhamma (Universitas Tadulako, 2021)
This study aims to describe the use of mysterious boxes and cards on physics learning outcomes of 11th grade students at SMA Negeri 2 Totikum. It was a qualitative research using a descriptive approach. The research subjects were 5 students. In this study, there were two types of data, quantitative and qualitative. Data collection techniques using observation, written tests, student response questionnaires and interviews. The results showed that the teacher's and student's activities when using the mysterious box and card were included in the very good category. As for the learning outcomes test, 2 people got very good learning outcomes, 2 people got good learning outcomes and 1 person got adequate learning outcomes. Furthermore, in responding to the use of mysterious boxes and cards in physics learning, it was shown that 4 people gave a very good response and 1 person gave a good response.